2015
DOI: 10.1159/000371511
|View full text |Cite
|
Sign up to set email alerts
|

Positive Reactions to Nickel on a Patch Test Do Not Predict Clinical Outcome of Nickel Alloy-Based Atrial Septal Defect Occluder Implantation

Abstract: Background: Patch testing is thought to be necessary prior to metal device implantation to rule out metal allergy-related complications; however, there are controversies over the effects of nickel allergy on the outcome of nickel alloy-based device implantation. Objective: This study aimed to evaluate the adverse events in a Korean population of nickel allergy patients who underwent atrial septal defect (ASD) closure with a nickel-titanium alloy-based device. Methods: We retrospectively reviewed the medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…In addition, for patients with a positive history to nickel allergy, patch testing is thought to be necessary prior to nitinol device implantation to rule out nickel contact allergy-related complications. However, in the study of Kim et al [8] , positive reactions to nickel in a patch test were not associated with adverse outcomes following closure of atrial septal defects with a nickel alloy-based device.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, for patients with a positive history to nickel allergy, patch testing is thought to be necessary prior to nitinol device implantation to rule out nickel contact allergy-related complications. However, in the study of Kim et al [8] , positive reactions to nickel in a patch test were not associated with adverse outcomes following closure of atrial septal defects with a nickel alloy-based device.…”
Section: Discussionmentioning
confidence: 90%
“…Conclusions: To the best of our knowledge, Formally, EBVs are contraindicated in patients with known allergies to nitinol or silicone [6] . In addition, there is controversy regarding the effects of nickel alloybased device implantation in patients with nickel contact allergy, since there is concern about the release of nickel after nitinol device implantation [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…[4,6] However, according to another study, allergic symptoms after device implantation were similar between nickel-allergic and non-nickel-allergic groups. [7] But negative trial was a retrospective analysis and number of patients was inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial thrombus was not reported in any patients, including 33 nonallergic patients. 4 However, this study has limited generalizability, particularly to other types of devices with different structures, nickel content, and nickel exposure. In this patient, the surgical specimen was noted to have significant inflammation and hypertrophied scar on visual inspection raising concern that a chronic inflammatory process may have played a role.…”
Section: Misra Et Al Late Thrombus Of Interatrial Septal Occludermentioning
confidence: 94%